Clinicopathologic study of breast lumps in Abakaliki, South Eastern Nigeria - Ugwu-Olisa, Ogbuanya Aloysius; Nnamdi, Anyanwu Stanley; Gregory, Nwigwe Chinedu; Festus, Iyare (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: Breast lumps are quite common, but the principal issue is differentiating malignant from the benign sub-groups. The determinants of histologic diagnosis are multifactorial, ranging from environmental, genetic to sex and age-related factors. This study aimed to document the spectrum of breast lumps in our environment. Materials and Methods: This is a descriptive prospective analysis of consecutive breast lumps biopsied at Federal Teaching Hospital Abakaliki, between December 2010 to November 2012. The data were analysed using statistical package for social sciences (SPSS) version 22.0 Results: A total of 302 patients with 359 breast lumps were seen, 298 females and 4 males giving male: female ratio of 1:75.The ages of the patients ranged between 16-82 years with a mean of 37.0 +/- SD 13.0. Majority (56.3%) of the patients had benign lumps. Fibroadenoma was the commonest (33.8%), followed closely by invasive ductal carcinoma (32.8%), then fibrocystic change (17.2%).The occurrence of breast cancer was strongly age-related, being 1 in 5 biopsies at 20-29 years and 3 in 5 biopsies at 40-49 years age groups. Over two-third (69.0%) of 132 patients with breast cancers were premenopausal. Majority (78.8%) of the 132 patients with breast cancer presented with advanced disease. At a median follow up of 9 months,13 (9.8%) and 6(4.5%) of 132 cancer patients developed recurrences and new cancer sites respectively. Conclusion: Most patients with breast complaints present with lumps and majority are benign, fibroadenoma being the commonest histology. Occurrence of breast cancer is strongly age-related with majority of cancer patients presenting late. Asian Journal of Medical Sciences Vol. 7(3) 2016 58-64